Effect of the functionalized π-bridge on porphyrin sensitizers for dye-sensitized solar cells: an in-depth analysis of electronic structure, spectrum, excitation, and intramolecular electron transfer. Issue 39 (21st September 2015) - Lu, Xiaoqing; Shao, Yang; Wei, Shuxian; Zhao, Zigang; Li, Ke; Guo, Chen; Wang, Weili; Zhang, Mingmin; Guo, Wenyue
Abstract : The effects of π-bridge on the structural and optoelectronic properties of porphyrin sensitizers were systematically elucidated. Abstract : A series of porphyrin sensitizers for dye-sensitized solar cells (DSSCs) have been systematically investigated by density functional theory (DFT) and time-dependent DFT (TD-DFT) in tetrahydrofuran (THF) solution. The effects of π-bridge length, heteroaromatic unit, longitudinal conjugation, and relative position of functionalized groups on the optical and electrical properties are elucidated by analyzing the geometry, electronic structure, electron excitation, spectrum, photo-induced intramolecular electron transfer (IET), and light-harvesting efficiency (LHE). Our results show that the increase in π-bridge length by the addition of phenyl groups distances the electron distribution of LUMO away from the anchoring group and sharply decreases the effective electron excitation at the long wavelength region. The introduction of heteroaromatics in the π-bridge, especially electron-deficient units, stabilizes LUMO levels and improves the light-harvesting capability and donor-to-acceptor IET characteristics significantly. The extension of longitudinal π-conjugation in the π-bridge broadens the B band and slightly strengthens and redshifts the Q band but results in undesired orbital overlap. Repositioning the phenyl/thiophene group away from carboxylic acid increases the energy gap but leads to more effective long-range IET processes with more electrons, longer distance, lower orbital overlap, and moderate transfer rate. Our results highlight the significant effect of the functionalized π-bridge on porphyrin sensitizers, and provide a new insight into the design and screening of sensitizers for DSSCs.